2017
DOI: 10.1039/c6ra28648h
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of nanocomposite film made from a jackfruit filum polysaccharide incorporating TiO2nanoparticles by photocatalysis

Abstract: Jackfruit filum polysaccharide (JFPS) was extracted and confirmed to contain neutral and acidic polysaccharides, largely composed of acidic polysaccharides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…As can be seen, the T d and Δ w increased, but the residue (%) decreased with the increase of TiO 2 NPs content from 0.5% to 2% in CH films. The result revealed that CH films incorporated with TiO 2 NPs significantly improved the thermal stability of CH films compared to the control film, which can be ascribed to the better thermal stability of TiO 2 when compared with CH and to good interaction between TiO 2 and CH …”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…As can be seen, the T d and Δ w increased, but the residue (%) decreased with the increase of TiO 2 NPs content from 0.5% to 2% in CH films. The result revealed that CH films incorporated with TiO 2 NPs significantly improved the thermal stability of CH films compared to the control film, which can be ascribed to the better thermal stability of TiO 2 when compared with CH and to good interaction between TiO 2 and CH …”
Section: Resultsmentioning
confidence: 95%
“…Degradation and glass transition temperatures of materials are an important property in selecting a packaging material, and TGA analysis enables a good insight into the specific thermal properties of polymeric materials . Thermal degradation temperatures ( T d , °C), weight loss (Δ w ), and residue of films are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations